Tales of Healers and Doctors: Enlighted Pedagogy and Modernization in Cuban Costumbrismo - Miguel Angel Pillado (Universitas Sanata Dharma, 2022)
The aesthetic movement known as costumbrismo burst during the 19th in Spain and Latin America, and it did so into various modes of artistic expression such as literature, painting, and lithography. In all cases, it aimed at reflecting on the way of life in a given society e.g. its folklore, its institutions, its mannerisms, its social types, etc. The present article delves into Cuban costumbrismo to expose the way in which local writers akin to this aesthetic movement exhibit the local population in correspondence with an ongoing and much desired process of modernization. Specifically, it examines four cuadros de costumbres (sketches of manners of costumbrista nature) that focus on two historically antagonistic social types in Cuba: the médico (the doctor) and the vieja curandera (the old female healer). It demonstrates that the representations of these figures do not only synthesize—at best—the way in which Cuban costumbrista authors managed a process of social and historical change brought about by the tension between local traditions and the emergence of modern scientific discourses as civilizing measures. In doing so, it also reveals the intentions of these authors to legitimize the place of literature in a modernizing world where scientific discourses were also gradually becoming the only authorized language for studying and analysing both the individual and the social body.